BacDive—the Bacterial Diversity Metadatabase - Söhngen, Carola (Oxford University Press, 2014)
BacDive—the Bacterial Diversity Metadatabase (http://bacdive.dsmz.de) merges detailed strain-linked information on the different aspects of bacterial and archaeal biodiversity. Currently (release 9/2013), BacDive contains entries for 23 458 strains and provides information on their taxonomy, morphology, physiology, sampling and concomitant environmental conditions as well as molecular biology. Where available, links to access the respective biological resources are given. The majority of the BacDive data is manually annotated and curated. The BacDive portal offers an easy-to-use simple search and in addition powerful advanced search functionalities allowing to combine more than 30 search fields for text and numerical data. The user can compile individual sets of strains to a download selection that can easily be imported into nearly all spreadsheet applications.